Fatal Outcome of COVID-19 Relapse in a Fully Vaccinated Patient with Non-Hodgkin Lymphoma Receiving Maintenance Therapy with the Anti-CD20 Monoclonal Antibody Obinutuzumab: A Case Report - Federica Calò; Lorenzo Onorato; Mariantonietta Pisaturo; Antonio Pinto; Loredana Alessio; Caterina Monari; Carmine Minichini; Manuela Arcamone; Alessandra Di Fraia; Luigi Atripaldi; Claudia Tiberio; Nicola Coppola (Vaccines, 2022)
Few data are available regarding the effectiveness of anti-SARS-CoV-2 vaccine in immunocompromised patients. Vaccination may have a suboptimal efficacy in this population, in particular if patients are exposed to anti-B-cell therapy. We report the virological and clinical characteristics of a patient with follicle center lymphoma under bimonthly maintenance therapy with obinutuzumab, an anti-CD20 monoclonal antibody. Despite three doses of BNT162b2 vaccine, the patient was infected by the SARS-CoV-2 Omicron variant. After an initial period of clinical and molecular remission due to early therapy with sotrovimab, the patient experienced a fatal relapse sustained by the same viral strain.